EMPLOYEE PERFORMANCE IMPROVEMENT TO ADDRESSING ASEAN ECONOMIC COMMUNITY. – CASE STUDY PLN MANADO - Rumokoy, Farlane S. (Journal of Asean Studies on Maritime Issues, 2016)
Asean Economics Community (ASC) is the challenge and opportunities to expand the company. The welfare benefits given to outsourced workers include, among other things, the payment of monthly wages in accordance with the prevailing Regional/Provincial Minimum Wage, which covers basic wages, transportation costs, overtime pay, holiday bonuses (THR), Jamsostek contributions, work uniforms, and other rights in accordance with the stipulations of the regulations pertaining to manpower, and as stipulated and regulated in the work contract between the Company and the third party which received jobs from PLN. Based on the data analysis using a multiple regression Reward System and Job Stress influence on Employee Performance at PT. PLN (Persero) Wilayah SULUTTENGGO Office Simultaneously.